2020
DOI: 10.1038/s41598-020-65721-7
|View full text |Cite
|
Sign up to set email alerts
|

Parthenium hysterophorus steps up Ca-regulatory pathway in defence against highlight intensities

Abstract: Parthenium hysterophorus exhibits tolerance to a great extent against abiotic stresses including high light intensities. in this study, P. hysterophorus was subjected to three different light intensities viz. control (CL, 250 µmol photons m −2 s −1), moderately high (ML, 500 µmol photons m −2 s −1) and high (HL, 1000 µmol photons m −2 s −1) for assessment of biochemical and physiological responses at 3 and 5 days after treatment (DAT). Proteomic responses were also observed at 5 DAT. Level of oxidative stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 68 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Among all the tested extracts for total antioxidant capacity (TAC), the P. hysterophorus leaf extract prepared at high temperature in methanolic solvents shown maximum antioxidant capacity. In a study done by Ahmad et al, total antioxidant capacity (TAC) of P. hysterophorus increased with increased duration of stress in leaves; the leaves exposed to high light (HL) showed maximum TAC as compared to leaves exposed to medium light (ML) [ 11 ]. The reduction potential of the P. hysterophorus extract was maximum in flower extract prepared in the methanolic medium at high temperature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the tested extracts for total antioxidant capacity (TAC), the P. hysterophorus leaf extract prepared at high temperature in methanolic solvents shown maximum antioxidant capacity. In a study done by Ahmad et al, total antioxidant capacity (TAC) of P. hysterophorus increased with increased duration of stress in leaves; the leaves exposed to high light (HL) showed maximum TAC as compared to leaves exposed to medium light (ML) [ 11 ]. The reduction potential of the P. hysterophorus extract was maximum in flower extract prepared in the methanolic medium at high temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Parthenium has been reported to inhibit the growth of other vegetation [ 10 ]. In a recent study by Ahmad et al, it is found that P. hysterophorus exhibits tolerance to great extent against abiotic stresses including high light intensities [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Here, bioinformatics and proteomic studies will be used to identify the P. hysterophorus leaf protein that corresponds to P20. [10]…”
mentioning
confidence: 99%